Suplementação de vacas leiteiras da raça holandesa com enzimas fibrolíticas - Barbosa, Douglas Kleiton (2017)
The growing global demand for food of animal origin has caused the intensification of primary production systems. In milk production system of this deepening can be characterized by the breeding and improvement in the nutritional management of animals. To maintain high production and provide the necessary concentration of nutrients is necessary to provide high amounts of concentrates, however, this can lead to certain anomalies in ruminal fermentation affecting the production and health of the animal. The use of digestive enzymes is gaining considerable space in the sector, in order to promote greater performance and animal health. The objective of this study is to evaluate the use of increasing doses of Fibrolytic enzymes diluted and applied in the diet of dairy cows Compost Barn system, and evaluate the performance of dairy cows. The research will be conducted on a dairy property located in the city of Two Neighbors, in southwestern Paraná. They will be evaluated in the experiment in statistical linear model in a period of 21 days with 14 days for diet adaptation and seven days of data collection on: production and milk composition. The animals selected for the experiment will weight approximately date of production and lactation.